Correlational analysis on physical and chemical contaminants of indoor air quality / Amalina Abu Mansor ... [et al.] - Abu Mansor, Amalina; Radzuan, Nurul Annisah; Abdullah, Samsuri; Che Dom, Nazri; Mohd Yatim, Siti Rohana; Mat Jusoh, Suriani; Zulkifli, Mohammad Fakhratul Ridwan; Ismail, Marzuki (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
The acceptable or good indoor air quality is important in minimizing the risk of getting any building- related illness especially for those staying indoors and working in the health center. This study assessed the IAQ in the health center of a university, involving physical and chemical parameters. The sampling points are at the entrance door, counter, four treatment rooms, dentist section, and waiting rooms. Sampling was conducted with 15-minutes intervals for each point starting from 0800 hours to 1700 hours for three days. Results show that the respirable suspended particulate (PM 10 ) concentrations (0.015-0.020 mg/m3 ), carbon monoxide (CO) (0.40 – 0.43 ppm), and relative humidity (62.7 -66.9%) comply with standard while temperature (21.9-23.6°C), CO 2 (969-1026 ppm), and air movement (0.01-0.18m/s) did not comply with the standard. Spearmen correlation showed that there was high negative correlation between relative humidity and temperature (r=0.685, p<0.05), CO (r=-0.776, p<0.01) and CO 2 (r=-0.776, p<0.05). Human respiration, diversity of indoor activities, and ventilation system issue are among the important factors in the reduction of IAQ.